Comunicación de la responsabilidad social empresarial por parte de las organizaciones en Ecuador. - Lojas Garcia, Paul Estuardo (My University, 2021)
In the development of this article, the qualitative method was used to analyze the communication pattern used by companies in Ecuador in order to determine the effectiveness of their channels when communicating the corporate social responsibility activities of which they are engaged. The objective that was raised focuses on identifying the way in which organizations in Ecuador make their Corporate Social Responsibility activities known and also; find or point out the most effective and efficient channels through which companies communicate their social activities. The results indicate that most of the organizations that were taken into account in this study use the platforms of Social Networks and Web Pages as channels to communicate their R.S.E activities to society at a national level. The article concludes with a more panoramic view of the communication tools that companies use to reach stakeholders and external groups, thus giving a better image of the organization in the market that carries out its activities, for more information, review the development of the article with a list of companies that will be the object of study and the results of the investigation will also be found.
En el desarrollo del presente artículo se hizo uso del método cualitativo para analizar el patrón comunicacional que usan las empresas en Ecuador con el fin de determinar la efectividad de sus canales al momento de comunicar las actividades de responsabilidad social empresarial de las cuales están comprometidas. El objetivo que se planteó se enfoca en identificar la forma en que las organizaciones en Ecuador dan a conocer sus actividades de Responsabilidad Social Empresarial y además; encontrar o señalar los canales más eficaces y eficientes con la cual las empresas comunican sus actividades sociales. Los resultados indican que la mayoría de organizaciones que se tomaron en cuenta en este estudio usan las plataformas de Redes Sociales y Páginas Web como canales para comunicar a la sociedad a nivel nacional sus actividades de R.S.E. Se concluye el artículo con una vista más panorámica de las herramientas de comunicación que utilizan las empresas para llegar a los stakeholders y a grupos externos dando así una mejor imagen a la organización en el mercado que desempeña sus actividades, para más información, revisar en el desarrollo del artículo con un listado de empresas que serán el objeto de estudio y se encontrará también los resultados los resultados de la investigación.
Keywords: REDES SOCIALES; COMUNICACIÓN; IMAGEN CORPORATIVA